Graduate and Continuing Medical Education of Placenta Accreta Spectrum - Feltmate, Colleen; Easter, Sarah R.; Gilner, Jennifer B.; Karam, Amer K.; Khourry-Callado, Fady; Fox, Karin A. (American Journal of Perinatology, 2023)
Surgical training experience in obstetrics-gynecology (OB-GYN) residency and fellowship training, particularly in open abdominal surgeries has declined over the last 2 decades. This is due, in part, due to a universal trend toward non-invasive treatments for gynecologic conditions once treated surgically. Management of placenta accreta spectrum (PAS) often requires complex surgical skills, including, but not limited to highly complex hysterectomy. The decline in surgical case numbers has fallen as the incidence of PAS has risen, which we anticipate will lead to a gap in critical skills needed for graduating obstetrician-gynecologists to able to safely care for people with PAS.
Keywords: medical education; simulation; surgical skills; placenta accreta spectrum; hysterectomy